Construction of Dual Cyclic Codes over F_{2}[u,v]/ < u^2, v^2 - v, uv - vu > for DNA Computation - Singh, Manoj Kumar; Singh, Abhay Kumar; Kumar, Narendra; Mishra, Pooja; Gupta, Indivar (Defence Science Journal, 2018)
Here, we assume the construction of cyclic codes over ℜ=F_{2}[u,v]/ < u^2, v^2 - v, uv - vu >. In particular, dual cyclic codes over ℜ= F_{2}[u]/ <u^2> with respect to Euclidean inner product are discussed. The cyclic dual codes over ℜ are studied with respect to DNA codes (reverse and reverse complement). Many interesting results are obtained. Some examples are also provided, which explain the main results. The GC-Content and DNA codes over ℜ are discussed. We summarise the article by giving a special DNA table.